2000
DOI: 10.1128/aem.66.5.1866-1870.2000
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Infectious Cryptosporidium parvum Oocysts in Mussels ( Mytilus galloprovincialis ) and Cockles ( Cerastoderma edule )

Abstract: Infective Cryptosporidium parvum oocysts were detected in mussels (Mytilus galloprovincialis) and cockles (Cerastoderma edule) from a shellfish-producing region (Gallaecia, northwest Spain, bounded by the Atlantic Ocean) that accounts for the majority of European shellfish production. Shellfish were collected from bay sites with different degrees of organic pollution. Shellfish harboring C. parvum oocysts were recovered only from areas located near the mouths of rivers with a high density of grazing ruminants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
1
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(59 citation statements)
references
References 24 publications
(19 reference statements)
2
55
1
1
Order By: Relevance
“…Up to 12.5 % of the samples analyzed contained Cryptosporidium oocysts. This rate is considerable high from a public health perspective and similar to those levels cited in previous reports (Gomez-Bautista et al, 2000;Lowery et al, 2001;Giangaspero et al, 2005). Moreover, water analysis in the area where the mussel samples were collected in the Chao Phraya River was also conducted.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Up to 12.5 % of the samples analyzed contained Cryptosporidium oocysts. This rate is considerable high from a public health perspective and similar to those levels cited in previous reports (Gomez-Bautista et al, 2000;Lowery et al, 2001;Giangaspero et al, 2005). Moreover, water analysis in the area where the mussel samples were collected in the Chao Phraya River was also conducted.…”
Section: Resultssupporting
confidence: 83%
“…In the naturally contaminated samples of Cryptosporidium oocysts, this paper reported 31.1 % of contamination and only C. parvum has been found. In another study, infective C. parvum oocysts were detected in mussels and cockle from a shellfish-producing region that account for the majority of European shellfish production (Gomez-Bautista et al, 2000). All these data suggested that mussels and cockles could act as a reservoir of C. parvum infections to humans (GomezBautista et al, 2000;Graczyk et al, 1998;Graczyk et al, 2001;Lowery et al, 2001).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…En invertebrados se ha detectado en moluscos bivalvos marinos (ostras, mejillones, berberechos) [13][14][15][16][17][18][19][20][21][22] , lo que sirve como indicador de contaminación fecal de las aguas. En Chile, el estudio de 642 moluscos bivalvos (choritos, ostras, almejas, machas) y muestras de agua salada obtenidas de playas de la Región de Valparaíso, usando microscopia y pruebas moleculares no ha detectado la presencia de ooquistes de Cryptosporidium como contaminante de agua ni mariscos (Neira P, datos no publicados).…”
Section: Correspondencia Aunclassified
“…Raw shellfish, e.g., molluscs, oysters, clams, scallops, and other marine life, in costal waters are increasingly being implicated as potential reservoirs for the transmission of the viable and infective stages of Cryptosporidium (2,8,13,16,19). Contamination is apparent mainly in near-shore waters and estuaries where human sewage is discharged and runoff from land exposed to animal manure occurs (18,25).…”
mentioning
confidence: 99%